(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Menopause is the natural cessation or stopping of a woman’s menstrual cycle and marks the end of fertility. Ovarian function declines can lead to undesirable alterations in metabolism, vascular endothelium function, fibrinolytic and coagulative properties of blood. Menopause may enhance risk for ischemic heart disease in women due to such altered properties of blood and vascular function. Aims and Objectives: To compare some haematological values in pre- and post-menopausal women to know the risk of vascular and ischemic heart disease in postmenopausal women. Materials and Methods: Blood samples were drawn in 50 women who have attained menopause and have weight of 55–60 kg and height of 150–160 cm and 50 control subjects who were disease-free women aged 35–40 years with matching weight and height. These women had natural menopause and were not subjected to any hormonal or surgical intervention. The vital parameters were recorded, and general examination was done. Results: There was a statistically significant increase in hematocrit, and there was no statistically significant change in platelet count, activated partial thromboplastin time (APTT), and prothrombin time (PT). Conclusion: A higher viscosity of blood can enhance the risk of coronary artery disease by elevating platelet aggregability and adhesiveness to sub-endothelium. However, the above effect may partially be offset by unchanged APTT and PT.